Comparison of soot radiation in diesel flame given by mathematical model and by experimental data - Ga, Bui Van; Nam, Tran Van; Linh, Nguyen Ngoc (Vietnam Journal of Mechanics, 2007)
An integral unidirectional model is established to calculate radiation heat transfer of Diesel flame in the open air and in combustion chamber of engine. Based on the temperature and soot fraction given by the flamlet theory and soot formation model of Tesner-Magnussen, radiation of soot particulate cloud at different positions of flame is determined and compared with experimental data obtained by the two-color method. The results show that the radiation given by the model is 203 lower than that produced by experiments on the stationary flame in open air. Soot radiation intensity in the Diesel engine increases in function of load and engine speed regimes and its maximum value (about 2000 kW/m2) is reached when the highest pressure is attained in combustion chamber.